A Systematic Review of Adaptive Learning Research in Physics Education in Indonesia - Muhammad Minan Chusni (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2022)
This study aimed to map publication topics and research interests based on the author’s keywords in an analysis of co-occurrence analysis from the Scopus database on adaptive learning research in physics education. This study used a systematic review method with primary data sources, namely, articles from scientific journals and proceedings indexed by Scopus from 2014 to 2021. Keyword restrictions were focused on adaptive learning with physics topics in Indonesia. The results of the study showed that the five main clusters related to adaptive learning, were machine learning, deep learning, algorithms, calculations, and students. Based on the results of the novelty analysis, areas becoming research trends in the realm of educational research were independent learning, instructional design, and curriculum to optimize adaptive learning. The results of this study could be used as a reference for further research focusing on developing and optimizing the potential of adaptive learning in Indonesia.